Patient outcomes in GuideLiner facilitated percutaneous coronary intervention stratified by the SYNTAX score: A retrospective analysis. (March 2019) - Liu, Shuangbo; Parr, Christopher; Zhang, Hannah; Elbarouni, Basem; Shah, Ashish; Kass, Malek; Ravandi, Amir
Objectives: To determine patient outcomes in GuideLiner facilitated percutaneous coronary intervention stratified by the SYNTAX score. Design: Single centre retrospective cohort analysis. Participants: A total of 540 consecutive cases facilitated by GuideLiner at a single center. Main outcome measures: Successful stent delivery, in-hospital, 30 day and 1 year mortality rates stratified by SYNTAX score. Results: The most common indication for GuideLiner was need for increased support for balloon or stent delivery (82%), 6% for non-coaxial guide, 9% for chronic total occlusion and 3% for selective vessel engagement. Successful stent delivery was achieved in 91% of all cases, with no complications occurred due to GuideLiner use. In-hospital, 30 day and 1 year mortality rates were 2.8%, 2.1% and 4.5%, respectively. The high SYNTAX group was associated with higher rates of initial TIMI score of 0–1; however, the final TIMI score rate of successful delivery and complications did not differ between groups. In-hospital and 1 year mortality rates were higher in the higher SYNTAX groups. Conclusions: The GuideLiner is an easy to use guide catheter extension system with high rates of success and low rates of complications, across all SYNTAX groups.